Moral education through dramatized storytelling: insights and observations from Indonesia kindergarten teachers - Rahiem, Maila Dinia Husni; Abdullah, Nur Surayyah Madhubala; Krauss, Steven Eric; Rahim, Husni (Society for Research and Knowledge Management, 2020)
This research looks at the insights and observations of kindergarten teachers in using stories and storytelling for Moral Education. The main research question is how teachers tell stories in order for children to learn moral values from the stories. This research applied qualitative research as a method of inquiry. Fourteen teachers were interviewed from two kindergartens in the suburbs of Jakarta and collected additional data through focus group discussions and observations. The data revealed that the teachers dramatize stories by: 1) telling or reading the stories in engaging and expressive ways; 2) using facial expression and body language; 3) using costumes, props, and technology. The findings indicate that dramatization can be an important catalyst for the successful use of storytelling in Moral Education in kindergartens. Dramatization is an approach that keeps children listening and able to learn from the stories. Dramatization helps children grasp the meaning of stories and helps them to learn moral values through the stories.